Barriers to Health Workers in Providing Health Education for Increase Degree of Health - Andi Satriana; Andi Bintang; Radiah Ilham; Dewi Mulfiyanti; Sumarni (PT Inovasi Pratama Internasional, 2022)
Health promotion is an effort to convey health messages to influence other people to improve their health status. In order for health messages to be accepted by the public, it needs to be supported by selecting appropriate media and increasing community empowerment. Therefore, Community Health Service activities were carried out regarding the creation of health promotion media. Lack of knowledge of nurses is one of the factors in the failure of health promotion. Knowledge of health workers regarding patient characteristics related to low health literacy will create gaps in the provision of health services. This research aims to describe the knowledge, attitudes, experiences and barriers of nurses regarding health literacy at the Bajoe Community Health Center, Bone Regency. The results of the activity show that public understanding regarding health promotion media has increased. Research conducted at the Bajoe Health Center, Bone Regency, had results showing that the majority of respondents were female, 28 (80%) respondents, with the majority age group being 20-30 years, 23 respondents (65.71%). Most of the respondents' work experience in hospitals was less than 10 years, namely 31 respondents (88.57%), while all respondents (100%) were domestic graduates. The majority of respondents had never heard of health literacy before, 34 (97.14%) respondents.